Perilaku Masyarakat Dalam Pengelolaan Wisata Hiu Paus Di Desa Labuhan Jambu Kecamatan Terano Kabupaten Sumbawa - Muslimah, Syohwatul; Sumitro, Sumitro (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The development of an area is very dependent on the tourism industry, because it can improve the nation's economy, especially as a source of regional income. Moreover, in rural areas, apart from being a source of village income, it can also open up new job opportunities for rural communities. Whale Shark Tourism is one of the tours in Labuhan Jambu Village, precisely on the south coast of Tarano District, Sumbawa Regency. Whale Shark Tourism is a form of effort made to encourage tourism in West Nusa Tenggara and one of the development activities for recreation and local economic development activities for the community, especially the community in Labuan Jambu Village. The method used in this research is descriptive qualitative with a simple purposive determination of informants. Data collection techniques; observation, interview and documentation. The data analysis technique; namely data reduction, data presentation, data interpretation, and drawing conclusions. Based on the foregoing, the results of this study are as follows; 1. Community social behavior that prioritizes and pays attention to the preservation of nature and its culture; 2. Friendly, disciplined and honest social behavior of the community as well as; 3. Social behavior of people who have the ability to cooperate with various parties.